268. Clinical Characteristics and Mortality Associated with Culture Positivity in Adult Inpatients with Sepsis: A 15-Year Cohort Study of 48, 706 Patients at a Tertiary Medical Center in Taiwan. (31st December 2020) - Chiang, Hsiu-Yin; Chen, Pei-Shan; Chi, Chih-Yu; Kuo, Chin-Chi
Abstract: Background: Culture-negative (CN) sepsis occurs in 30 60% of sepsis patients. Understanding CN sepsis is crucial for treatment optimization. We used an electronic medical records (EMR)-based surveillance proposed by Rhee et al. to identify patients with sepsis meeting Sepsis-3. We aimed to describe the trend of sepsis and mortality, and to study the characteristics and mortality associated with culture positivity. Methods: This cohort study included adult (>=18 years) inpatients with first-time sepsis who were admitted to our hospital during 2003–2017 (Figure 1 ). Sepsis was identified using clinical indicators of presumed infection and concurrent acute organ dysfunction. Culture-positive (CP) sepsis were those whose blood grew non-commensal organisms for > = 1 blood draw and those whose blood grew commensal organisms for > = 2 blood draws. Mortality were ascertained by the National Cause of Death Database. Multivariable Cox proportional hazard model was used to evaluate the effect of culture positivity on all-cause mortality. Figure 1. Selection Process of the Study Population (N = 48, 706). Results: Of 48, 706 adult inpatients with first-time sepsis, 41, 304 (84.8%) were CN. The sepsis rate increased from 4.6% to 8.7%, while in-hospital mortality significantly decreased from 30.2% to 14.5% (Figure 2 ). Patients with CN sepsis tended to be younger, male, less diabetes, liver cirrhosis but more cardiovascular disease, and received systemic antibiotic within 14 days prior (Table 1 ). Serum biochemical profiles of procalcitonin, hs-CRP, and lactate were significantly lower in CN sepsis. Mechanical ventilation and respiratory site of infection were more likely to be presented in CN sepsis. Overall, the mortality (in-hospital, 7-day, 30-day, 1-year) was lower in CN sepsis. After adjusting for confounders, culture positivity was significantly associated with 7-day mortality (aHR 1.21; 95% CI 1.08, 1.37) (Table 2 ). Figure 2. The Trend of Sepsis Rate (A) and In-hospital Mortality (B) of Adult Inpatients with Sepsis, 2003–2017 at CMUH. Table 1. Baseline Demographic and Clinical Characteristics of the Adult Inpatients with Sepsis, 2003–2017 at the CMUH (N = 48, 706). Table 2. Hazard Ratio (95% Confidence Interval) for Mortality Associated with Culture-Positive Sepsis. Conclusion: Sepsis rate increased while the mortality decreased, indicating the improvement of sepsis management in the past 15 years. The clinical characteristics of CN and CP sepsis were comparable, except for the lower inflammatory markers found in CN sepsis. Patients with CP sepsis had 21% higher risk of 7-day mortality. Next, we will link with National Health Insurance Database to examine admission history and antibiotic use in other institutions. Disclosures: All Authors : No reported disclosures